2019
DOI: 10.1101/563312
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrated Phosphoproteomics and Transcriptional Classifiers Reveal Hidden RAS Signaling Dynamics in Multiple Myeloma

Abstract: A major driver of multiple myeloma is thought to be aberrant signaling, yet no kinase inhibitors have proven successful in the clinic. Here, we employ an integrated, systems approach combining phosphoproteomic and transcriptome analysis to dissect cellular signaling in multiple myeloma to inform precision medicine strategies. Collectively, these predictive models identify vulnerable signaling signatures and highlight surprising differences in functional signaling patterns between NRAS and KRAS mutants invisibl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Alternatively, it may suggest that not all Ras mutations uniformly activate MAPK signaling. Indeed, this has been recently confirmed by phosphoproteomics in myeloma cell lines (130). In contrast, FGFR3 mutations appear to be a more potent inducer of MAPK signaling and are mutually exclusive with NRAS and KRAS mutations (130, 131).…”
Section: Genetic Events Of Progression In Mgus and Myelomamentioning
confidence: 67%
“…Alternatively, it may suggest that not all Ras mutations uniformly activate MAPK signaling. Indeed, this has been recently confirmed by phosphoproteomics in myeloma cell lines (130). In contrast, FGFR3 mutations appear to be a more potent inducer of MAPK signaling and are mutually exclusive with NRAS and KRAS mutations (130, 131).…”
Section: Genetic Events Of Progression In Mgus and Myelomamentioning
confidence: 67%
“…RAS-dependent activation of mTORC1 appears to be a prevalent form of pathogenic RAS signaling in MM and is distinct from RAS obliquely activating mTORC1 through activation of PI3-K (34). Our observations provide mechanistic insights to explain the paucity of active MEK signaling in many RAS-dependent MM tumors (7,8) and the underwhelming clinical response to MEK inhibitors in MM patients (9,10). However, we found that combinations of mTORC1 and MEK1/2 inhibitors were exceptionally synergistically toxic to RASdependent MM cell lines in vitro and nearly eliminated tumor growth in xenograft mouse models of MM.…”
Section: Discussionmentioning
confidence: 79%
“…RAS can signal through a number of effector pathways, perhaps most characteristically by activation of the classical MAP kinase (MAPK) pathway through RAF, MEK and ERK. Despite the high frequency of RAS mutations, the majority of MM tumors harboring RAS mutations have no detectable MEK activity by immunohistochemistry staining (7) or analysis of MAPK-dependent transcription (8), and MEK inhibitors have only had modest success treating MM patients in the clinic (9,10). These findings suggest that RAS-dependent activation of the classical MAPK pathway is not the sole mode of RAS signaling in malignant plasma cells and point to an unidentified role for oncogenic RAS signaling in this disease.…”
Section: Introductionmentioning
confidence: 97%